Efficient cell surface labelling of live zebrafish embryos: wash-free fluorescence imaging for cellular dynamics tracking and nanotoxicity evaluation. Issue 14 (12th March 2019) - Jia, Hao-Ran; Zhu, Ya-Xuan; Xu, Ke-Fei; Pan, Guang-Yu; Liu, Xiaoyang; Qiao, Ying; Wu, Fu-Gen
Abstract : We developed a red-fluorescent stain capable of achieving wash-free plasma membrane imaging in vitro and in vivo . Abstract : Imaging the dynamics and behaviors of plasma membranes is at the leading edge of life science research. We report here the development of a universal red-fluorescent probe Chol–PEG–Cy5 for wash-free plasma membrane labelling both in vitro and in vivo . In aqueous solutions, the fluorescence of Chol–PEG–Cy5 is significantly quenched due to the intermolecular resonance energy transfer (RET) between neighbouring Cy5 moieties; however, upon membrane anchoring, the probes undergo lateral diffusion in lipid bilayers, resulting in weakened RET and turn-on fluorescence emission. We demonstrate that Chol–PEG–Cy5 enables rapid, stable and high-quality in vitro cell surface imaging in a variety of mammalian cells. Additionally, with the assistance of three-dimensional (3D) image reconstruction, we achieve for the first time the whole-mount in situ fluorescence imaging of the epidermal cell surfaces of live zebrafish embryos, which cannot be realized by conventional plasma membrane probes due to the presence of the surface-covering mucus barrier. This novel technique encourages us to track the cellular dynamics of the epidermis during embryonic development with 3D visualization. Moreover, we also develop a new method to evaluate the epidermal toxicity of nanomaterials ( e.g., gold nanoparticles and graphene oxide nanosheets) toward zebrafish embryos using this fluorescent probe.